Sustainability Education in English Language Classes: Pre-Service Teachers’ Readiness - Ida Bagus Gde Phalaguna (Universitas Al-Qolam Malang, 2026)
This study investigates how prepared pre-service English teachers are to incorporate sustainability education into language instruction in accordance with the Sustainable Development Goals (SDGs) of the UN. The study, which was carried out at the State Hindu University of I Gusti Bagus Sugriwa Denpasar, used a convergent mixed-approach design, combining surveys, interviews, and lesson plan analysis to evaluate participants' sustainability-related knowledge, attitudes, and teaching methods. While most responders have a rudimentary awareness of sustainability, mostly in terms of the environment, few are able to incorporate these ideas into their lesson plans in a meaningful way, according to the findings. Despite this discrepancy, interview data revealed that participants were very motivated to learn and apply sustainability concepts, suggesting a solid basis for more training. The restricted availability of sustainability information was corroborated by lesson plan analysis, indicating a gap between awareness and pedagogical implementation. According to the report, English teacher education programs urgently need to explicitly incorporate Education for Sustainable Development (ESD). Language schools can develop linguistic and global citizenship skills by giving aspiring teachers the means and assurance to incorporate sustainability into language instruction. The results add to the expanding body of research on eco-pedagogy in ELT and provide useful suggestions for curriculum improvement in programs that prepare future teachers.